The Role Of Expropriation Clauses In Protection And Promotion Of Foreign Investments In Renewable Energy: An Essential But Overlooked Legal Consideration - Ghaziani, Moosa Akefi; Ghaziani, Mohammad Akefi (UI Scholars Hub, 2021)
Today the world is tackling climate change. The global threat of energy poverty along with the growing need for energy has escalated this crisis. The promotion of renewable energy sources is widely known as the main solution to this challenge. Many International and regional agreements address various aspects of renewable energy development such as trade, transit, security, and investment. Foreign investment is recognised as a crucial prerequisite for the global deployment of renewable energy, since not all States have the financial and technological potentials to develop this sector. Various investment agreements are signed to facilitate and promote investments. These instruments contain a mixture of obligations that have direct or indirect effects. Expropriation provisions which are often crystallised in the form of ‘a duty not to expropriate’ are among these obligations. This article analytically describes the legal aspects of this standard and proposes the trends that can better protect the foreign investments in this sector; a factor without which the foreign investors would normally be reluctant to invest. It concludes that restricted police power, guarantees of transfer, and a full compensation standard that entails the payment of compound interest are the prominent legal features that can best perform this task.